Race and Subprime Loan Pricing - Ruben Hernandez; Michael Owyang; Andra Ghent (European Regional Science Association (ERSA), 2011)
In this paper we investigate whether race and ethnicity influenced subprime loan pricing during 2005, the peak of the subprime mortgage expansion. We combine loan-level data on the performance of non-prime securitized mortgages with individual- and neighborhood-level data on racial and ethnic characteristics for metropolitan areas in California and Florida. Using a model of rate determination that accounts for predicted loan performance, we evaluate the presence of disparate impact and disparate treatment from race and ethnicity on rate-setting behavior across the most popular subprime mortgage products. In contrast with previous studies of the subprime market, we find evidence of adverse pricing effects for black and Hispanic borrowers.
Keywords: 330